2018
DOI: 10.22302/iopri.jur.jpks.v26i3.63
|View full text |Cite
|
Sign up to set email alerts
|

EFEKTIVITAS FLUBENDIAMIDA DALAM PENGENDALIAN ULAT API Setothosea asigna Van Eecke, ULAT KANTUNG Metisa plana Walker, DAN PENGGEREK TANDAN Tirathaba rufivena Walker SERTA PENGARUHNYA TERHADAP AKTIVITAS KUMBANG PENYERBUK Elaeidobius kamerunicus Faust.EFEKTI

Abstract: Flubendiamida merupakan insektisida baru yang memiliki selektivitas tinggi terhadap serangga dari kelompok Lepidoptera. Penelitian dilakukan untuk melihat pengaruh aplikasi flubendiamida terhadap tingkat mortalitas ulat api S. asigna, ulat kantung M. plana, dan penggerek tandan T. rufivena pada tanaman kelapa sawit menghasilkan. Dampak aplikasi flubendiamida terhadap aktivitas serangga penyerbuk E. kamerunicus juga turut diamati pada penelitian ini. Aplikasi flubendiamida dilakukan secara langsung pada tajuk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…Earlier studies in Malaysia, performed in a mineral and in a peat soil, also showed that repeated application of B. thuringiensis was essential to reduce T. rufivena infestation [2,6]. Meanwhile, repeated application of synthetic insecticide to control T. rufivena population was also reported [9,25,26,27]. However, chemical insecticide is not recommended since it had negative impact on the activity and population of E. kamerunicus [10,11,12,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies in Malaysia, performed in a mineral and in a peat soil, also showed that repeated application of B. thuringiensis was essential to reduce T. rufivena infestation [2,6]. Meanwhile, repeated application of synthetic insecticide to control T. rufivena population was also reported [9,25,26,27]. However, chemical insecticide is not recommended since it had negative impact on the activity and population of E. kamerunicus [10,11,12,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…The homogeneous spray solution will give maximum results. The fogging application was strongly influenced by the homogeneity of the spray solution, the determination of the active ingredients, the fogging machine, and the weather conditions when fogging applications [7].…”
Section: The Mortality Rate In Upper Frondsmentioning
confidence: 99%
“…Bahan aktif seperti deltametrin, sipermetrin, lamda sihalotrin, diazinon, dan asefat dapat diaplikasikan untuk pengendalian ulat api (Susanto et al, 2012). Insektisida berlabel hijau berbahan aktif klorantraniliprol atau flubendiamida merupakan alternatif insektisida yang lebih direkomendasikan penggunaannya karena relatif aman terhadap musuh alami dan serangga penyerbuk (Prasetyo, Sunindyo, & Susanto, 2015;Priwiratama, Rozziansha, & Prasetyo, 2018;Rozziansha, Prasetyo, Pradana, & Susanto, 2019).…”
Section: Strategi Pengelolaan Ledakan Hama Minor Ulat Api Kecil DI La...unclassified